Enhanced Electrocatalytic Activity of Branched Pd Nanostructures Decorated Conducting Polymer Nanofibers for Alkaline Fuel Cells. (2018) - Ghosh, Srabanti; Bera, Susmita; Karmakar, Naomi; Basu, Rajendra N.
Abstract: Conducting polymer nanostructures having anisotropic morphology and rich redox properties, employed as support for palladium metal catalysts for electrooxidation of ethanol. Polypyrrole nanofibers have been first synthesized using soft oxidative templates and consequently, a unique Pd-branched structure was nucleated on the polymer surface by photo-reduction method. Polymer supportedelectrocatalystsdemonstratedexcellentethanol oxidation activity (EOR)compared to commercial carbon supported catalysts Pd/Cin terms of current density. This work demonstrates a new and facile approach for the synthesis of electrocatalysts with both the enhanced activity and durability for fuel cell applications.